An Original L‐shape, Tunable N‐Heterocyclic Carbene Platform for Efficient Gold(I) Catalysis. (8th May 2019) - Tang, Yue; Benaissa, Idir; Huynh, Mathieu; Vendier, Laure; Lugan, Noël; Bastin, Stéphanie; Belmont, Philippe; César, Vincent; Michelet, Véronique
Abstract: The synthesis and characterization of original NHC ligands based on an imidazo[1, 5‐ a ]pyridin‐3‐ylidene (IPy) scaffold functionalized with a flanking barbituric heterocycle is described as well as their use as tunable ligands for efficient gold‐catalyzed C−N, C−O, and C−C bond formations. High activity, regio‐, chemo‐, and stereoselectivities are obtained for hydroelementation and domino processes, underlining the excellent performance (TONs and TOFs) of these IPy‐based ligands in gold catalysis. The gold‐catalyzed domino reactions of 1, 6‐enynes give rise to functionalized heterocycles in excellent isolated yields under mild conditions. The efficiency of the NHC gold 5 Me complex is remarkable and mostly arises from a combination of steric protection and stabilization of the cationic Au I active species by ligand 1 Me . Abstract : Breitband‐Liganden : Die Synthese und Charakterisierung von NHC‐Liganden basierend auf einem Imidazo[1, 5‐ a ]pyridin‐3‐yliden(IPy)‐Molekülgerüst mit einem angrenzenden Barbitursäure‐Heterocyclus sowie deren Verwendung als gezielt abstimmbare Liganden wird beschrieben. Für Gold‐katalysierte C‐N‐, C‐O‐ und C‐C‐Bindungsbildungen werden hohe Effizienzen beobachtet.